Applications of polymer-based membranes in the treatment of skin wounds: An integrative review (Research, Society and Development, 2022)
Objective: To investigate the healing potential of skin wounds and its influence on treatment time with the use of polymer-based membranes. Methodology: To reach the intended objective, the study carried out research based on an Integrative Literature Review, through articles in the search bases in publications indexed in the following Virtual Health Library (BVS) and Pubmed databases, from 2018 to 2022 , through health descriptors with the Boolean operator AND: polymers, healing, wounds. Results: As a result, it was understood that the use of polymers in skin wounds has been used as a chemical joint, in order to increase the structural integrity of the membranes. The membranes used in the studies allowed an important decrease in the pain condition of the treated patients, without the occurrence of high infections. However, consolidation techniques need to occur for the length of stay. Conclusion: In cases where skin wounds are exaggerated, these techniques may have cytotoxic tendencies, preventing resorption and causing material failures. positive or not in healing.